2000
DOI: 10.1291/hypres.23.277
|View full text |Cite
|
Sign up to set email alerts
|

Oral Taurine Supplementation Prevents the Development of Ethanol-Induced Hypertension in Rats.

Abstract: YOKOYAMATaurine is known to lower blood pressure in essential hypertension and some experimental hypertensive models. Taurine has also been reported to activate aldehyde dehydrogenase and to inhibit the elevation of plasma acetaldehyde concentration after ethanol intake. Because acetaldehyde, the first metabolite of ethanol, is suspected to be responsible for many adverse effects of alcohol consumption, we examined the effect of taurine supplementation on ethanol-induced hypertension and abnormalities in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Puddey et al 83 reported a BP elevation of B10 mm Hg and decreases in the level of phospholipids and the ratio of unsaturated/saturated fatty acids in the aorta and kidney after the chronic administration of alcohol to rats. Harada et al 84 also observed increases in the BP and platelet-free calcium concentration with ethanol consumption (15%) in Wister Kyoto rats.…”
Section: Experimental Studiesmentioning
confidence: 88%
“…Puddey et al 83 reported a BP elevation of B10 mm Hg and decreases in the level of phospholipids and the ratio of unsaturated/saturated fatty acids in the aorta and kidney after the chronic administration of alcohol to rats. Harada et al 84 also observed increases in the BP and platelet-free calcium concentration with ethanol consumption (15%) in Wister Kyoto rats.…”
Section: Experimental Studiesmentioning
confidence: 88%
“…It is known as a conditionally essential amino acid, which is present in the brain, heart, liver, neutrophils, retina and kidneys of mammals in high concentrations [2][3][4]. It acts as an antioxidant, xenobiotic conjugant, osmoregulator, intracellular calcium flux regulator, bile acid conjugator, neuromodulator, cell membrane stabilizer and plays an important role in cell proliferation and viability [3][4][5]. Taurine is known to have regulatory activities in gastrointestinal tract including…”
Section: Editorialmentioning
confidence: 99%
“…The antihypertensive effects of taurine have been demonstrated in several experimental models (Fujita and Sato 1984 ;Harada et al 2000 ;Nara et al 1978 ) . Studies in vitro showed that taurine relaxed pre-constricted rabbit ear artery (Franconi et al 1982 ) , rat aorta (Ristori and Verdetti 1991 ) , and rat mesenteric artery (Li et al 1996 ) .…”
Section: Discussionmentioning
confidence: 99%